The Impact of AI on Education: Innovative Tools and Trends - Msekelwa, Dr Patrick Zingisa (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
Every year, digital technologies appear in every industry. The new, developing technologies offer both advantages and disadvantages. The following are some recent examples of cutting-edge innovations in technology: data science, cybersecurity, block chain technology, artificial intelligence, machine learning, quantum learning, Internet of Things (IoT), 5G and 6G networks, hyper automation, cloud computing, robotics, and natural language processing. AL and ML combined with other cutting-edge, popular technologies have the potential to yield the positive outcomes and contribute to a greener future. Personalized medicine, drug development and predictive diagnostics using large scale data sets are all areas where machine learning might be beneficial to physicians. Students studying mechanical engineering must have a solid understanding of emerging trends such as autonomous vehicles. The potential of AV to create new, improved lifestyle and revolutionize urban planning and transportation has attracted a lot of interest. A research utilized a quantitative technique to further his research. A questionnaire was used to collect data from different participants, and 120 students from different fields in higher education sector were chosen at random. According to research, students who used popular technologies acquired more sophisticated abilities that will increase their output at work. Technology is always changing because it takes ongoing training to keep up with the latest development. The issue of the digital divide will be resolved by ongoing training.